Asparagus breeding: Future research needs for sustainable production - Drost, Daniel (Frontiers in Plant Science, 2023)
Productivity in asparagus (Asparagus officinalis L.) is determined in part by 1) the selection of superior, adaptive genetics, 2) matching the selected genetics to the production environment, and 3) managing the crop production system in ways to maximize harvest potential that are sustainable, profitable, and efficient. Over the last 100 years, a considerable effort by asparagus researchers has gone into breeding superior genetic lines, testing those in numerous locations, and studying how asparagus responds to a multitude of inputs (fertilizers, irrigation, fungicides, herbicides, insecticides). Farmers worldwide have benefited from all of these improvements. However, as we look to the future, we need to change our research approaches to deal with widely accepted limitations to asparagus growth that if left unanswered will further erode the long-term sustainability and profitability of the crop. This paper will briefly review the historical content of asparagus research, and open a discussion on how to refocus international research efforts to breed superior plant materials to meet future challenges.